DEVELOPMENT OF EDUCATION SYSTEMS IN THE FIELD OF STUDENTS TOWARDS SUPERIOR MADRASAS IN MTS. MUALLIMIN UNIVA MEDAN - Sari Harahap, Hotni (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
This study discusses: 1. How is the concept of an education development system in the field of student affairs leading to superior madrasas in MTs. Muallimin UNIVA Medan? 2. What are the aspects of developing the education system in the field of student affairs towards superior madrasas in MTs. Muallimin UNIVA Medan?This study uses a naturalistic qualitative approach. The term naturalistic shows that the implementation of this research does occur scientifically, as it is, and cannot be manipulated by circumstances and conditions, emphasizing natural descriptions. By this nature, the involvement of researchers is required directly at the research location.The research results show that: The concept of developing a quality system in the field of student affairs was carried out at the Madrasah Tsanawiyah Muallimin UNIVA Medan, which was designed by the head of the Madrasa by referring to government regulations, the statutes and bylaws of the Alwashliyah organization, and referring to the needs of madrasah stakeholders, deputy head of the madrasah section students are responsible for student management, as well as assisted by the person in charge of each self-development program for students, teachers and other staff through direct instructions from the head of the madrasah which have been carried out in accordance with established procedures. Planning regarding student management is prepared on the basis of madrasah capabilities and meets the needs of students and the demands of the times. Aspects of developing the education system towards superior madrasah include: a) fostering the learning process of students related to the teaching and learning process in the classroom b) fostering extracurricular and intracurricular student activities at Madrasah Tsanawiyah Muallimin UNIVA Medan, c) evaluating the results of student activities that carried out at Madrasah Tsanawiyah Muallimin UNIVA Medan carried out directly by the head of the madrasa and WKM in the student affairs sector and assisted by teachers and other staff, with the aim of ensuring the implementation of the student planning program that has been carried out, and monitoring deviations that occur.